Influence of coolant pressure on the wear and tool life of gun drills in deep drilling of 24CrMoV5-5 steel - Ivković, Milan; Djurović, Strahinja; Kočović, Vladimir; Džunić, Dragan; Djordjević, Aleksandar; Mitrović, Slobodan; Petrović Savić, Suzana (Journal of Production Engineering, 2025)
In modern material processing industries, the constant need for increased efficiency and precision drives ongoing research aimed at optimizing technological parameters. The presented study aims to analyze excessive wear and chipping of gun drills during the deep drilling process of 24CrMoV5-5 steel. The experiment was conducted on a horizontal deep drilling machine, model T30-2-500 (TBT Tiefbohrtechnik GmbH+Co), under real production conditions. The investigation included the performance analysis of both factory-reground and subsequently reground drills, with the number of tests enabling a detailed comparison across different process regimes. The process parameters were systematically varied in three phases, with a focus on increasing the coolant pressure from 50 to 60 bar, while other conditions, such as spindle speed and feed rate, remained constant. The results indicate that increasing coolant pressure allows for more efficient cooling, stabilization of temperature fluctuations in the cutting zone, and improved chip evacuation, directly leading to reduced chipping and more uniform tool wear. Consequently, this extends the service life of the drills and preserves the high precision of the machined surface. The obtained results provide valuable guidelines for optimizing deep drilling parameters, highlighting the importance of properly adjusted cooling conditions in industrial machining. Future research will focus on integrating additional processes, including variations in cutting speed, the application of different cooling techniques, and the implementation of intelligent tool condition monitoring systems, aiming to achieve an optimal balance between process efficiency and tool longevity.